REDESIGN WEBSITE PT MARS GEARITAMA DENGAN METODE USER CENTERED DESIGN (UCD) - Siti Najmia Ihvasyani (2022)
PT Mars Gearitama is a company in the field of domestic and international freight (cargo) that uses a website to publish information about the company and can also request logistics quotas. However, the PT Mars Gearitama website currently only focuses on delivering company information and services without paying attention to how the website can help potential clients. The information contained on the current website has not been updated for a long time. Many changes regarding vital information such as company name, office location, warehouse location and the latest services that have not been updated on the website. Other problems are that the website interface is outdated and not updated, the quota request feature is still too complex for users to use and the functionality of the login feature. It is therefore necessary to research the user experience level, this needs to be achieved in order for the website to be fully useful for the users. The purpose of this study is to compare the level of user experience including the level of usability before and before the website redesign. This study uses the User Centered Design (UCD) method with data collection using the User Experience Questionnaire (UEQ). The output of this research is in the form of recommendations for the design of a new user interface site based on the UCD steps. The results of the website redesign evaluation obtained an increase in user experience on the overall scale with the results that the attractiveness scale increased the average value to 2,13 points, the perspicuity scale 2,18 points, the efficiency scale 2,01 points, the dependability scale 1,98 points, the stimulation scale is 1,96 points and the novelty scale is 1,93 points. The six variables experienced an increase and got a very good value or "excellent" which means that the redesign is able to overcome existing website problems.